Sex + Corruption = Sexortion - Amalia SYAUKET; Dwi Seno WIJANARKO (International Journal of Environmental, Sustainability, and Social Science, 2022)
Transparency International includes sextortion or sexual extortion in the Global Corruption Barometer Asia. According to the data above, Indonesia ranks first in the country with the number of cases of sextortion highest in Asia. The forms of corruption that most often adorn every government organization, which occur the most and are vulnerable to involving state officials, are extortion, gratification, and bribery. Other more surprising facts from GCB Asia 2020 research a new indicator, namely sextortion, and Indonesia ranks first in the highest sextortion cases in Asia. This term is still very common, which reveals that corruption is not just a matter of money. As for the problems that will be answered with a descriptive qualitative approach, first, in the perspective of criminal law, are the provisions governing sextortion adequate? Second, what can be done to prevent the prevalence of sextortion? This study found that first, the regulation of sextortion is adequate in Indonesian criminal law, which is identical and congruent with abuse of power. Secondly, prevention efforts are in the form of a moralistic system and community empowerment. Novelty: Integrate sextortion into the anti-corruption movement in the form of an anti-sexual harassment program to achieve wider awareness that sextortion is a form of corruption.